Respuesta :
2x^2-17x-33=0 let's complete the square, add 33 to both sides
2x^2-17x=33 make the leading coefficient equal to one, divide all by 2
x^2-8.5=16.5 halve the linear coefficient, square it, and add that to both sides
x^2-8.5+18.0625=34.5625 now left side is a perfect square
(x-4.25)^2=34.5625 take the square root of both sides
x-4.25=±√34.5625 add 4.25 to both sides
x=4.25±√34.5625 so the factors are:
(x+4.25+√34.5625)(x+4.25-√34.5625)
2x^2-17x=33 make the leading coefficient equal to one, divide all by 2
x^2-8.5=16.5 halve the linear coefficient, square it, and add that to both sides
x^2-8.5+18.0625=34.5625 now left side is a perfect square
(x-4.25)^2=34.5625 take the square root of both sides
x-4.25=±√34.5625 add 4.25 to both sides
x=4.25±√34.5625 so the factors are:
(x+4.25+√34.5625)(x+4.25-√34.5625)
[tex]2x^2-17x-33 : \text{Factor}
[/tex]
[tex]a(x- \dfrac{-b+ \sqrt{b^2-4ac} }{2a}, x-\dfrac{-b- \sqrt{b^2-4ac} }{2a} [/tex]
[tex]2(x- \dfrac{17+ \sqrt{(-17)^2}-4*2*-33 }{2*2}, x-\dfrac{17- \sqrt{(-17)^2}-4*2*-33 }{2*2} [/tex]
[tex]2(x- \dfrac{17+ \sqrt{553} }{ 4}, x- \dfrac{17- \sqrt{553} }{ 4})[/tex]
[tex]a(x- \dfrac{-b+ \sqrt{b^2-4ac} }{2a}, x-\dfrac{-b- \sqrt{b^2-4ac} }{2a} [/tex]
[tex]2(x- \dfrac{17+ \sqrt{(-17)^2}-4*2*-33 }{2*2}, x-\dfrac{17- \sqrt{(-17)^2}-4*2*-33 }{2*2} [/tex]
[tex]2(x- \dfrac{17+ \sqrt{553} }{ 4}, x- \dfrac{17- \sqrt{553} }{ 4})[/tex]